Prevalence of pressure injury on the medical wards of public general hospitals in Kuwait: a national cross-sectional study - Talal ALFadhalah; Marjan Lari; Gheed Al Salem; Shaimaa Ali; Hamad Al Kharji; Hossam Elamir (BMC, 2024)
Abstract Background Pressure injury is a severe problem that can significantly impact a patient's health, quality of life, and healthcare expenses. The prevalence of pressure injuries is a widely used clinical indicator of patient safety and quality of care. This study aims to address the research gap that exists on this topic in Kuwait by investigating the prevalence of pressure injuries and preventive measures on the medical wards of the country's public general hospitals. Methods A cross-sectional research design was adopted to measure the point prevalence of pressure injuries on 54 medical wards in the public general hospitals. Data, including variables pertaining to hospitals, patients, pressure injuries and preventive practices, were collected using an online form. The data were processed and analysed using Microsoft Excel and SPSS 23 (α level = 0.05). Analysis provided an overview of patient, pressure injury characteristics and preventive measures, and the relationships between the patient and pressure injury characteristics and the prevalence of pressure injuries. A model for predicting the determinants of pressure injury prevalence was constructed from a linear regression analysis. Results The mean national prevalence of pressure injury was 17.6% (95% CI: 11.3-23.8). Purely community-acquired pressure injuries represent the majority of pressure injuries nationally (58.1%). Regarding preventive measures, "pressure injury assessment on admission" has been provided to 65.5% of patients. Correlation analysis revealed that the only statistically significant correlation with the prevalence of hospital-acquired pressure injury was "pressure injury assessment on admission", which was strongly negative (ρ = −0.857). Therefore, this was the only variable included in the regression analysis as a predictor of pressure injury prevalence (Beta = 0.839). The results showed many statistically significant differences between hospitals with respect to the variables studied. Conclusions The national pressure injury prevalence is high compared to the global rate. The higher percentage of purely community-acquired pressure injuries requires particular attention. Many risk factors for the development of pressure injuries are public health concerns, and effective mitigating strategies are needed. Further research is required to assess the knowledge, attitude, and behaviour of nurses with respect to pressure injuries, and to evaluate preventive and management practices.